Preparation and luminescent properties of zinc sulfoselenide thin films - Slyotov, М.М.; Slyotov, О.М. (Physics and Chemistry of Solid State, 2019)
The preparation of zinc sulfoselenide heterolayers is considered. The possibility of obtaining a hexagonal modification of the crystal lattice by the method of isovalent substitution was shown. The λ-modulated optical reflection was studied and the parameters of the energy structure of α-ZnSe, α-ZnS, α-ZnS0.45Se0.55 were determined. It has been established that the obtained heterolayers are characterized by intense photoluminescence with a quantum yield η = 8–12% in the blue-violet region. It is formed by constituent bands, the nature of which is determined by the annihilation of bound excitons and interband transitions of free charge carriers. It is shown that the selection of temperature regimes allows obtaining radiation with ħωm maxima in the violet 2.80 eV, blue 2.70 eV and green 2.45 eV spectral regions. It is determined by the generation-recombination transitions involving donor and acceptor states formed by intrinsic point defects of the crystalline lattice , і Zni, respectively. The models of radiative recombination are discussed.